Cartilage regeneration effect of orally administered Zingiber officinale against MIA-induced osteoarthritis in rats - Ganabadi, Shanti; Fakurazi, Sharida (2010)
Osteoarthritis (OA) develops when the cartilage that protects the bone gradually destroyed within the synovial joint. The condition progresses slowly and the initial changes of cartilage includes pitting, fibrillation and cleft formation, which will eventually becomes ulcerated and irregular [1]. In the mature articular cartilage, chondrocyte is the only type of cells that is responsible for production and maintenance of extracellular matrix. Therefore, any reduction in their density will play a role in the development of OA [2]. Currently, there are no commercially available drugs definitively proven to modify the progression of OA. Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for the treatment of OA pain. But the long term use of such drugs may cause suppression of platelet aggregation, erosions and ulcerations in upper gastrointestinal tract mucosa [3]. Such adverse side effects may be ameliorated by the use of plant extracts alternatives. Zingiber officinale (ZO) is one such candidate that is believed to be potential to reduce pain and symptom caused by OA. ZO has been shown to suppress cyclooxygenase, lipooxygenase metabolites and arachidonic acid [4]. Therefore this study was conducted to compare and quantify the histopathological changes of cartilage between ZO treated rats and control rats in Monosodium idoacetate (MIA)-induced OA. Twenty adult male Sprague Dawley rats were divided into control (n=10, treated with normal saline) and treatment group (n=10, treated with ZO extract). Prior to treatment, all rats were injected with 60mg/ml MIA intra-articularly in their right knee joints to induce OA [3]. All rats were treated by administration of the suggested therapies using feeding catheter for 28 days. At day 28, rats were sacrificed. Whole right and left knee joints were dissected free from all soft tissues. Joints were fixed in 5% neutral buffered formalin for 2 days and subsequently decalcified with 10% formic acid for 5 days. Joints were dehydrated in ethanol, embedded in paraffin, sectioned and stained with either hematoxyline and eosin or with Safranin-O fast green stain. Evaluation of OA changes in the knees was assessed with the aid of histopathological scores [5]. The data is analysed with Kruskal-Wallis and Mann-Whitney U tests. ZO treated group showed significantly low degeneration of the cartilage and significantly less severity of the subchondral bone compared to control group. This study concluded that oral administration of ZO revealed the curative effects of the extract on OA joints.